Public sector reform in Malaysia – addressing the inequalities? - Wan Abdullah, N.R. (2010)
In the mid - 1980s, there emerged a ‘paradigm shift’ with the adoption of the market ideology in the light of changed situations and changing policy priorities of the government of the Malaysian government. As the role of government changed from direct intervention to an indirect and supportive one the public sector was called for reforms to enable it to perform its new and emerging roles effectively. The public service responded by introducing new reform measures, the major reform being the privatization policy which falls within the New Public Management (NPM) framework. The government adopted the Privatization Masterplan —encompassing sectors such as telecommunications, airlines, railway, electricity, port, and postal services—to reduce public spending, relieve the state’s fiscal burden, and strengthen market forces. Despite its contributions to economic growth, the implementation of privatization policy has remained a contentious issue for a number of reasons.